OP0256 Changes of Microrna Expression in Lymph Node Stromal Cells of Rheumatoid Arthritis Patients. (10th June 2014) - Ospelt, C.; Hähnlein, J.; Gay, R.E.; Tak, P.P.; Gerlag, D.M.; Gay, S.; Van Baarsen, L.G.M.
Abstract : Background: Lymph node stromal cells (LNSC) build the scaffold that enables migration and interaction of lymphocytes in the lymph node. More recently, it has been shown that during inflammation LNSC play a crucial role in shaping the immune response and maintaining tolerance. However, little is known about the underlying molecular mechanisms. Objectives: In the current study we analyzed the expression of microRNAs in LNSC from healthy individuals, RA patients as well as anti-CCP positive arthralgia patients with a high risk to develop RA. Methods: Needle biopsies of inguinal lymph nodes were strained through a 70μm nylon mesh and the resulting stromal part was cultured in DMEM with 10% FCS. Adherent cells were passaged 4 times before total RNA was isolated. RNA was reverse transcribed with specific microRNA stem loop primers and loaded onto TaqMan® Low Density Arrays (Life technologies, MicroRNA Panel A). The data were analyzed on the Expression Suite software using RNU48 as endogenous control, and differentially expressed microRNAs were re-measured in single-assay reactions. Results: 4 microRNAs appeared differentially regulated between healthy individuals (n=5) and RA patients (n=6) with a p-value <0.05. Intriguingly, all of the significantly changed microRNAs belonged to the same cluster, namely miR-503, miR-424, miR-450a and miR-542. Increased expression of these microRNAs in RA patients could be confirmed in single measurements and was stable independent of the endogenous control used (RNU44, snU6, RNU6B). All of these clustered microRNAs were upregulated in RA patients, but their regulation differed in arthralgia patients. While a trend towards increased expression of miR-503 was also seen in arthralgia patients (RNU44 p=0.0307; snU6 p=0.0936; RNU6B p=0.140), the other microRNAs did not differ between the healthy and the arthralgia group. Interestingly, in 2 out of 6 arthralgia patients, the expression of miR-450a and miR-524 was equally high as in RA patients. Conclusions: LNSC of RA patients have specific changes in their microRNA profile with upregulation of a microRNA cluster on chromosome X q26.3. Studying these miRNAs in a larger cohort of patients, further follow up of the arthralgia patients and functional analysis of these microRNAs will clarify the role of the lymph node microenvironment on arthritis development and bring valuable insights into pathophysiological mechanisms of disease development. Acknowledgements: IMI BTCure n° 115142, EURO-TEAM n° 305549, IAR, Dutch Arthritis Foundation grant 11-1-308, Netherlands Organisation for Health Research and Development (ZonMw) Veni project 916.12.109 Disclosure of Interest: C. Ospelt Grant/research support: IMI BTCure, IAR, EURO-Team, J. Hähnlein: None declared, R. Gay Grant/research support: IMI BTCure, IAR, EURO-Team, P. Tak Employee of: GSK, D. Gerlag Employee of: GSK, S. Gay Grant/research support: IMI BTCure, IAR, EURO-Team, L. Van Baarsen: None declared DOI: 10.1136/annrheumdis-2014-eular.4383